2016
DOI: 10.7205/milmed-d-15-00246
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Interactions of Military and Law Enforcement Bullets at 1.5 and 3 Tesla

Abstract: Military and law enforcement non-nickel- or nonsteel-containing bullets appear to be safe for patients in MRI system at 1.5 and 3 T. On the other hand, nickel- and steel-containing bullets exhibit movements that are considered potentially unsafe for patients in an MRI environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, several studies have demonstrated that non-nickel and non-steel based bullets are safe to undergo MRI. 13 - 15 Venous lead levels are routinely drawn on GSW patients in order to obtain baseline values. If spinal instability is present, bracing is offered or surgical intervention consisting of instrumentation and fusion with removal of bullet fragment if encountered.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have demonstrated that non-nickel and non-steel based bullets are safe to undergo MRI. 13 - 15 Venous lead levels are routinely drawn on GSW patients in order to obtain baseline values. If spinal instability is present, bracing is offered or surgical intervention consisting of instrumentation and fusion with removal of bullet fragment if encountered.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that ferromagnetic bullets have the potential to migrate up to 10 cm in gelatine structures and show significant rotation at both 1.5T and 3T . However, nearly all nonsteel and nonnickel containing bullets showed no migration or rotation in magnetic fields up to 7T . Although one study found nonsteel bullets could migrate and rotate, the authors suggested that this could be due to metallic impurities…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bullets are MRI compatible but this is not true with shotgun pellets. 35 -38 If a patient is being imaged with MRI and there is ballistic debris in close proximity to critical neurovascular structures, a very thorough risk benefit analysis should be performed with particular attention paid to the effect bullet motion might have.…”
Section: Imaging Assessmentmentioning
confidence: 99%